2016
DOI: 10.1016/j.homp.2015.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Inhalation therapy with M1 inhibits experimental melanoma development and metastases in mice

Abstract: Altogether these data suggest M1 is an efficient candidate for melanoma therapy to be considered for future clinic studies as this study is the first supporting the idea that melanoma patients may benefit with the treatment. The treatment with M1 provides advantages considering the highly-diluted properties and a cost effective alternative to costly chemotherapeutic approaches with, if any, lower toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 35 publications
2
12
0
Order By: Relevance
“…For a number of years, scientists and physicians have considered that the anti-tumor effects of high dilutions were due solely to immune system activation. However, we have found that treatment with M1 in vivo did not affect immune cell numbers in metastatic melanoma-bearing mouse lungs (35). Additionally, the effects of M1 seem to occur irrespective of lymphocyte-mediated immunity (unpublished data).…”
Section: In Vitro Attenuation Of Classic Metastatic Melanoma-related mentioning
confidence: 84%
See 3 more Smart Citations
“…For a number of years, scientists and physicians have considered that the anti-tumor effects of high dilutions were due solely to immune system activation. However, we have found that treatment with M1 in vivo did not affect immune cell numbers in metastatic melanoma-bearing mouse lungs (35). Additionally, the effects of M1 seem to occur irrespective of lymphocyte-mediated immunity (unpublished data).…”
Section: In Vitro Attenuation Of Classic Metastatic Melanoma-related mentioning
confidence: 84%
“…Finding cost-effective treatments for selected diseases has been a priority in our research group. Over the past years, we have investigated, in vitro (24)(25)(26)(27)(28)(29)(30)(31) and in vivo (32)(33)(34)(35)(36), the effects of highly diluted natural complexes (HDNCs). Lately, we have focused on two specific HDNCs, namely M1 and M8.…”
Section: In Vitro Attenuation Of Classic Metastatic Melanoma-related mentioning
confidence: 99%
See 2 more Smart Citations
“…47 Antitumour effects, directly by killing tumour cells or acting via immune system activation, were demonstrated after experimental tumour-bearing mice treatment with 'Lymphomyosot', 48 Hydrastis canadensis, Lycopodium, Thuja, 49 Calcarea carbonica, 50 M8 complex, 20 and M1 complex. 51 Cell culture has also been used to demonstrate homeopathic preparations' cytotoxicity to tumour cells but not to normal cells. Anti-proliferative effects of Sarsaparilla on ACHN (human renal adenocarcinoma), Ruta graveolens on COLO-205 (human colorectal carcinoma), and Phytolacca decandra on MCF-7 (human breast carcinoma) cells were shown.…”
Section: Discussionmentioning
confidence: 99%